III International Conference on Health Sciences and its contribution to scientific innovation and academic development in Medical Sciences - García, Mario A. (Revista Gregoriana de Ciencias de la Salud, 2024)
The second issue of the Gregorian Journal of Health Sciences is presented, a space dedicated to the dissemination of knowledge and research in Health Sciences. This number has a special meaning, as it coincides with the recent celebration of the III International Conference on Health Sciences "Science, medical education and health for social transformation and sustainable development", organized by the Medicine program of the Universidad San Gregorio de Portoviejo. This event has left an indelible mark on our academic and professional community.